POTENSI WISATA DANAU TIMBANG BUNGA PENGANTIN DESA SUNGAI SORIK KABUPATEN KUANTAN SINGINGI - ", Lesmeri; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Lake Timbang Bunga pengantin is a natural lake attractions that has beautiful natural scenery. This lake is an area that has the potential to be developed into featured tourist attractions in Kuantan Singingi District. This research aims to describe the potential of Lake Timbang Bunga Pengantin. This study uses a qualitative method with a descriptive approach. Data collection is done by observation technique, interview, documentation and literature study. The results of the study show that; Lake Timbang Bunga Pengantin has the beautiful natural scenery attraction, clean and fresh air, clear water and beautiful rice field views. Various activities that can be done on this lake like; enjoy the beauty of natural panorama, playing paddle ducks, play mini canoes, take photos, and exercise.  Keywords : Tourism Potential, Tourism Attraction, Development